1981
DOI: 10.1159/000153200
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Serum Protein and Enzyme Polymorphisms in the District of L’Aquila (Italy)

Abstract: A random sample of more than 500 subjects collected in the district of I’Aquila (Italy) has been studied for the following genetic markers: ADA, EsD, G-6-PD, 6-PGD, SOD-A, Hp, C3. The gene frequencies of all the systems examined were similar to those observed in Rome. Rare variants have been found for 6-PGD, C3 and SOD-A. The last one showed an electrophoretic pattern different from the only other variant so far observed in the Italian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
1

Year Published

1982
1982
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
1
1
1
Order By: Relevance
“…The results in dicate that the Greek population has fre quencies comparable to other Caucasian populations, although variants of the GOTs locus were found in this survey but not in samples analyzed from Great Bri tain and the FRG [7,10,12], [9] and in red cells [II] from diverse populations; this matter was discussed by Donald [9]. The Northern Greek popula tion has an EsD2 frequency of 0.158, which is about the same as that of studies in Italy [4,8], but slightly higher than those reported from other European popula tions [11]. The EsD2 allele appears to show an increasing frequency from Northern to Southern Europe [4, 8, I 1, and this study].…”
Section: Electrophoresissupporting
confidence: 63%
“…The results in dicate that the Greek population has fre quencies comparable to other Caucasian populations, although variants of the GOTs locus were found in this survey but not in samples analyzed from Great Bri tain and the FRG [7,10,12], [9] and in red cells [II] from diverse populations; this matter was discussed by Donald [9]. The Northern Greek popula tion has an EsD2 frequency of 0.158, which is about the same as that of studies in Italy [4,8], but slightly higher than those reported from other European popula tions [11]. The EsD2 allele appears to show an increasing frequency from Northern to Southern Europe [4, 8, I 1, and this study].…”
Section: Electrophoresissupporting
confidence: 63%
“…The distribution of Gc types in Central Sardinia was statistically different from those observed for Trentino and Veneto populations [5][6][7], The Central Sardinian sample pre sented a lower frequency of the C3S allele than the continental Italian populations (range: 0.808-0.826) [8][9][10] and than two South Sardinian samples [10,11], There were significant differences between our sample and the populations from Tuscany [10] and Abruzzi [9]. …”
contrasting
confidence: 75%
“…Serum samples were typed by electrophor esis on Cellogel (Chemetron, Milano), us ing a tris-glycine buffer (pH 8.4) according to Grunbaum and Zayac [4] for Gc and a tris-glycine buffer (pH 8.6) according to Germenis et al [5] for C3. The observed frequency of the Gc1 al lele was in accordance with those given for many other Italian populations (Italian populations range: 0.715-0.775) [6,7], There were no significant differences be tween our sample and the other Italian populations.In the C3 polymorphism, the South Sardinia sample presented a lower fre quency of C3S allele than the L'Aquila population [8,9], but there were no signi ficant differences, and a frequency of C3S allele quite similar to that found in a popu lation sample from Rome [9], …”
mentioning
confidence: 49%